Outcomes of emergency or urgent mitral valve repair in patients with papillary muscle rupture and active infective endocarditis. (September 2020) - Li, Jun; Wang, Chunsheng; Zhou, Tianyu; Sun, Yiping; Zhu, Kai; Zhai, Junyu; Sun, Yongxin; Wei, Lai; Lai, Hao; Ding, Wenjun; Hong, Tao
Background: Emergency or urgent surgery is often required in patients with papillary muscle rupture and active mitral valve infective endocarditis. The aim of this study was to analyze the outcomes of patients with active endocarditis who underwent emergency or urgent mitral valve repair. Methods: From 2005 to 2014, 154 ischemic mitral regurgitation patients and 41 infective endocarditis patients underwent mitral valve repair in our institution; 23 had emergency operations due to papillary muscle rupture, and 18 with active infective endocarditis underwent urgent surgery. Results: Cardiopulmonary bypass time (141.4 ± 43.3 versus 145.3 ± 46.5 min) and crossclamp time (77.7 ± 34.1 versus 79.2 ± 33.0 min) were similar in the papillary muscle rupture and elective ischemic mitral regurgitation subgroups, and major postoperative complications were comparable. Hospital mortality was 17.4% in the papillary muscle rupture subgroup and 8.4% in the elective ischemic mitral regurgitation subgroup. Cardiopulmonary bypass time (103.6 ± 37.0 versus 75.5 ± 20.8 min) and crossclamp time (61.7 ± 21.2 versus 45.3 ± 18.0 min) were significantly longer in infective endocarditis patients. There were no major complications or hospital deaths. Eight years postoperatively, overall survival was 94.4% and 86.5% in the papillary muscle rupture and elective ischemic mitral regurgitation subgroups, respectively ( p  = 0.730). Overall survival was 100% in both infective endocarditis subgroups. Conclusion: The feasibility and effectiveness of emergency or urgent mitral valve repair in patients with papillary muscle rupture and active infective endocarditis are satisfactory. Early and mid-term outcomes are comparable to those of elective operations.